Closing the divide: insights into cloud-based learning for students in rural areas - Nurshamshida Md Shamsudin; Mahadir Ladisma; Roslaili Anuar; Cheong, Tau Han; Akmal Ahmed Kamal (Penerbit Universiti Kebangsaan Malaysia, 2023)
The digital revolution, characterized by the proliferation of cloud-based educational platforms, promises to democratize access to quality education. However, the benefits of this revolution are not uniformly distributed, with rural areas often lagging due to infrastructural and socio-economic disparities. This study seeks to explore the perspectives of students in rural areas regarding cloud-based education and to understand its potential to bridge the educational divide. Utilizing a mixed-methods approach, data was collected from 500 students across ten rural districts through surveys, followed by in-depth interviews with a subset of 50 participants. Preliminary findings suggest that while a majority of students nnectivity and lack of adequate devices. Interestingly, students who had experienced cloud-based learning expressed a favorable attitude, highlighting its flexibility and the diverse range of resources. Yet, they also voiced concerns over limited teacher-student interaction and feelings of isolation. The research underscores the need for infrastructural development in rural areas, tailored instructional designs that foster community engagement, and teacher training to effectively harness the potential of cloud-based education. In conclusion, cloud-based education emerges as a promising avenue to address educational challenges in rural settings. However, its successful implementation requires a holistic approach, addressing both technological barriers and pedagogical adaptations to meet the unique needs of rural students.